POLA KOMUNIKASI ORANGTUA DAN ANAK DALAM PENGGUNAAN APLIKASI YOUTUBE - Kartika Sari Yudaninggar (Jurusan Ilmu Komunkasi FISIP Universitas Jenderal Soedirman, 2021)
Parents in the concept of being the parties who play a role and have control in the use of devices on their children. This study seeks to analyze how communication patterns between parents and the technology using the YouTube application. Specifically, this research uses the YouTube application because YouTube is the most active social media in Indonesia and most accessed in 2019. Furthermore, the method used is descriptive qualitative, involving informants who have children aged 2-6 years and use YouTube as their children's viewing. Then structured interviews to determine the communication patterns carried out by the informants. Referring to the three patterns of family communication in the relationship between parents and children proposed by Baumrind, the results of this study are that there are several patterns of communication made by informants regarding the use of YouTube in children, including determining the duration and viewing schedule, selecting content, and regarding involvement and mentoring. There are no specific guidelines found regarding the communication patterns of parents and children in using YouTube. This uniqueness occurs due to various factors, including the different needs and values of each family.